The Effect of Drill Assisted CTL Model on the Mathematical Knowledge Competence of Fifth Grade Elementary School Students - Dewa Ayu Shri Laksmi Prama Dewi; I Wayan Wiarta; Didith Pramunditya Ambara (Universitas Pendidikan Ganesha, 2026)
Mathematics learning in elementary schools often faces the problem of students’ low conceptual understanding because the learning process tends to be procedural and is less connected to students’ real life contexts. The practice activities provided are not structured continuously, resulting in suboptimal reinforcement of concepts. This study aims to analyze and examine the effect of implementing the Contextual Teaching and Learning (CTL) model assisted by drills on the mathematical knowledge competence of fifth grade elementary school students. The study employed a quantitative approach with a quasi experimental design, involving two classes as samples: an experimental class (CTL + Drill) and a control class (conventional). Data were collected through multiple-choice tests and analyzed descriptively and inferentially using a t-test. The results indicate that the implementation of CTL assisted by drills significantly improves conceptual understanding, students’ active engagement, and mastery of the material through structured practice. The average mathematics competence score of the experimental class was higher than that of the control class (80.6 vs. 65.3) with a significant difference (p < 0.05). In conclusion, the CTL model assisted by drills is proven effective in enhancing elementary students’ mathematical knowledge competence. The implication is that teachers can use this model to strengthen concepts, increase engagement, and improve mathematics learning outcomes.